“Pengaruh Model Pembelajaran Communicative Language Teaching (CLT) terhadap Keterampilan Berbicara Bahasa Indonesia Sekolah Dasar: “Pengaruh Model Pembelajaran Communicative Language Teaching (CLT) terhadap Keterampilan Berbicara Bahasa Indonesia Sekolah Dasar - Aria Arifaa; Baharudin; Ayu Reza Ningrum (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The ability to speak is one of the fundamental aspects of language learning that enables learners to express ideas, feelings, and opinions effectively. In the context of Indonesian language learning, speaking skills reflect how well students can use language appropriately and politely in daily communication. However, many primary school students still experienced difficulties in expressing their thoughts due to limited vocabulary and low self-confidence. To address these issues, this study applied a literature review focusing on the use of the Communicative Language Teaching (CLT) approach to improve Indonesian speaking skills among primary school students. The data were obtained from various national and international journals indexed in Scopus and Google Scholar. The reviewed studies revealed that CLT encouraged active participation through interactive activities such as discussions, role-playing, and presentations that made students more confident and expressive in speaking. The synthesis results show that CLT effectively enhances vocabulary mastery, promotes meaningful communication, and develops students’ ability to speak fluently and accurately in real-life contexts. It also highlights that teachers’ roles as facilitators and motivators are essential in creating a communicative and enjoyable classroom atmosphere. Therefore, the CLT approach is proven to be an effective and practical model for improving students’ speaking competence in Indonesian language learning at the primary level.